2015
DOI: 10.1111/jsm.13071
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections and First Sexual Intercourse Age in Adolescents: The Nationwide Retrospective Cross-Sectional Study

Abstract: Introduction Sexually transmitted infections (STIs) are major causes of medical and psychological problems globally, while adolescents in South Korea have recently shown rapid changes in sexual behaviors. Aims We aimed to examine the association between the age of first sexual intercourse and the experience of STIs among adolescents. Additionally, in which specific time period would more likely to get infected from sexual int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
9
0
5
Order By: Relevance
“…Estos resultados difieren de lo reportado en una revisión sistemática que refiere que las adolescentes con inicio sexual temprano presentan más comportamientos sexuales de riesgo, tales como mayor cantidad de parejas sexuales e infecciones de transmisión sexual, el no uso de anticoncepción, tener o repetir un embarazo a temprana edad 3 . El usar o no usar un método anticonceptivo no presentó diferencias según la edad de inicio de la actividad sexual; sin embargo, las adolescentes con inicio sexual temprano aumenta casi dos veces el riesgo de un embarazo no planificado, lo que concuerda con otros estudios 3,4,5,6 . Esto hace pensar que si bien las adolescentes que inician relaciones sexuales de forma temprana lo hacen aparentemente usando algún anticonceptivo, estos no serían lo suficientemente efectivos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estos resultados difieren de lo reportado en una revisión sistemática que refiere que las adolescentes con inicio sexual temprano presentan más comportamientos sexuales de riesgo, tales como mayor cantidad de parejas sexuales e infecciones de transmisión sexual, el no uso de anticoncepción, tener o repetir un embarazo a temprana edad 3 . El usar o no usar un método anticonceptivo no presentó diferencias según la edad de inicio de la actividad sexual; sin embargo, las adolescentes con inicio sexual temprano aumenta casi dos veces el riesgo de un embarazo no planificado, lo que concuerda con otros estudios 3,4,5,6 . Esto hace pensar que si bien las adolescentes que inician relaciones sexuales de forma temprana lo hacen aparentemente usando algún anticonceptivo, estos no serían lo suficientemente efectivos.…”
Section: Discussionunclassified
“…3,4,5,6 . Algunos estudios han determinado como inicio sexual coital, vaginal o anal temprano o precoz, aquel que ocurre antes de los 14 o 15 años, sin haber un consenso 3,4 .…”
Section: Introductionunclassified
“…(7) The earlier the age of first sexual debut, the chance of experiencing STI is more. (8) In a study from Humsafar Trust Bombay, it is found that the mean age of first sexual intercourse among MSM is around 24.8 years. (4) Adolescents with STI have an increased risk of subsequent HIV infection, when compared to adolescents without STI.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual intercourses significantly increase the vulnerability to Sexually Transmitted Infections (STIs) in adolescence, being this prevalence of 7.4% in male and 7.5% female adolescents, from 2007 to 2013 in South Korea, a country considered developed in relation to Brazil (2) .…”
Section: Introductionmentioning
confidence: 99%